Analisis Determinan Terhadap Kinerja Karyawan PT Perkebunan Nusantara IV - Insan, Muhammad Yalzamul; Saputra, Edi Saputra; Ramadhany, Nadhiea (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
This research was conducted to determine the effect of work dicipline, Work Motivation on Employee Performance at PT. Perkebunan Nusantara IV (Persero) Medan. The sample in this study used the simple random sampling method. In this study, the entire population was not taken as a sample. Researchers only took 81 employees. This study uses primary data processed with IBM Statistics SPSS 26. The data analysis technique used is multiple linear regression models and moderating. The results of this study indicate that work dicipline and work motivation simultaneously have a positive and significant effect on the performance of employees of PTPN IV Medan. Partially, each work dicipline and work motivation have a positive and significant effect on the performance of employees of PTPN IV Medan. The t test shows that work dicipline has a tcount of 3.291 and a significance of 0.001, Work Motivation has a tcount of 2.986 and a significance of 0.004. Job Satisfaction and Work Motivation have a Fcount of 20,462 > Ftable of 2.72   Keywords : Job Satisfaction, Work Motivation, Employee performance